2011
DOI: 10.5214/ans.0972.7531.1118409
|View full text |Cite
|
Sign up to set email alerts
|

Painful diabetic neuropathy: an update

Abstract: Diabetes, a silent killer, is a leading cause of neuropathy. Around 50% of diabetic patients develop peripheral neuropathy in 25 years. Painful diabetic neuropathy manifests as burning, excruciating, stabbing or intractable type of pain or presents with tingling or numbness. The pathophysiology of this condition is due to primarily metabolic and vascular factors. There is increase in sorbitol and fructose, glycated endproducts, reactive oxygen species and activation of protein kinase C in the diabetic state. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 1 publication
0
61
0
1
Order By: Relevance
“…NSAIDs have shown narrow therapeutic benefits, 73,74 but more work is needed to ascertain their benefits along with other pharmacological agents. 75 As a major inflammatory mediator in the diabetic milieu, COX-2 is implicated in diabetic neuropathy, and a more targeted approach to therapy will certainly prove more effective. Unlike nonselective NSAIDs, 76,77 COX-2 inhibitors show promise, with protection against nerve dysfunction and nerve fiber loss 78 as well as attenuated mechanical hyperalgesia 79 in experimental diabetes.…”
Section: Pge 2 In Hypertension and Diabetesmentioning
confidence: 99%
“…NSAIDs have shown narrow therapeutic benefits, 73,74 but more work is needed to ascertain their benefits along with other pharmacological agents. 75 As a major inflammatory mediator in the diabetic milieu, COX-2 is implicated in diabetic neuropathy, and a more targeted approach to therapy will certainly prove more effective. Unlike nonselective NSAIDs, 76,77 COX-2 inhibitors show promise, with protection against nerve dysfunction and nerve fiber loss 78 as well as attenuated mechanical hyperalgesia 79 in experimental diabetes.…”
Section: Pge 2 In Hypertension and Diabetesmentioning
confidence: 99%
“…Although several randomized controlled trials have shown that TCAs are effective for patients with post‐herpetic neuralgia and diabetic peripheral neuropathy, there are concerns with adverse effects such as orthostatic hypotension, urinary retention and drowsiness, so it may not be the appropriate choice for elderly patients . There are also concerns with the potential of TCAs to predispose patients to cardiac arrhythmias and heart block . Besides TCAs, other therapies that have been evaluated include opioids, anticonvulsants and topical treatments (lidocaine patch, capsaicin and ketamine).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Oxidative stress arises in the hyperglycemic state from an increased production of reactive oxygen species, which is due to the auto-oxidation of the excess glucose and a failure in antioxidant mechanisms [60]. These oxygen-free radicals mediate endothelial dysfunction by inhibiting nitric oxide, leading to ischemic nerve damage.…”
Section: α-Lipoic Acidmentioning
confidence: 99%